Accountability of Traditional Islamic Boarding School in Aceh - Muhammad Ichsan Adnan; Aliamin Aliamin; Ratna Mulyany (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to see how accountability in traditional Islamic boarding school in Aceh. This research was conducted using a qualitative approach through in-depth interviews with related parties. Observation, documentation and literature review were also carried out to deepen the discussion and research results. This study was conducted by interviewing five informants. The results of the study found that accountability of traditional pesantren in Aceh has shown good accountability. However, there are some aspects that needs to be improved so that organizational accountability quality can be better. Traditional Islamic boarding school need to improve the quality of financial reporting.